Weed Management in Cotton - J. A. Ferrell; G. E. MacDonald; Pratap Devkota (EDIS)
A successful weed control is essential for economical cotton production. Weeds compete with cotton for moisture, nutrients, and light. The greatest competition usually occurs early in the growing season up to 8 weeks after emergence. Late-season weeds, while not as competitive as early-season weeds, may interfere with insecticide applications, may cause harvesting difficulties, and add seed in the soil seedbank. https://edis.ifas.ufl.edu/wg003